Nature-related vocabulary: its effectiveness and influence in artistic depiction in the Holy Quran - Houichi, Oum Kalthoum (El Omda in Linguistics and Discourse Analysis, 2025)
The ability of the Qur’anic expression to move the soul, emotions, intellect, and imagination testifies to its uniquely distinctive features. Imagery is a key tool employed in the Qur’an’s language to present scenes vividly, bring images closer to understanding, and animate life with its mysteries, movements, and dimensions, giving it a tangible, sensory form and the quality of life itself. It transforms the Qur’an into a source of life to which the human being turns and in which they find the truth of their self and the essence of their existence. What draws the attentive reader to artistic imagery in the Holy Qur’an is the dense presence of nature-related vocabulary, which reflects extreme precision in description, coherence in composition, and strong evocative power. This is what the article seeks to examine and clarify. It also aims to show the contribution of nature-related terms in forming images and the extent of their effectiveness and influence in the artistic depiction of the Holy Qur’an.